Resistencia a plagas invertebradas - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
During 1984 evaluations for resistance to Empoasca kraemeri, Apion godmani, and seed-infesting bruchids were continued. Some bean accessions were also evaluated for their reaction to the slug Vaginulus plebeius. Several red-and white-seeded selections from crosses for resistance to E. kraemeri reached yield levels near the best black lines under pest attack; mulatinho lines have shown the highest levels of resistance. Breeding for resistance to Apion godmani is being conducted in close collaboration with national bean programs in Central America; APN lines have been developed which are well adapted and show high levels of resistance. Breeding for resistance to seed-infesting bruchids (Acanthoscelides obtectus and Zabrotes subfasciatus) involved F3 selections from additional crosses between commercial bean types and wild Phaseolus vulgaris sources of resistance. Concerning the slug V. plebeius, CIAT has commited resources for the evaluation of germplasm for resistance to this pest and the search for natural enemies. In one test performed with whole plants infested with 2 slugs/plant for 24 h in the glasshouse, significant differences were found in consumption of bean foliage among accessions of P. vulgaris and other plant species. (CIAT)